Islamic Preaching and Its Significance in Realizing the Virtuous City (Al-Madinah Al-Fadhilah) in the Perspective of Al-Farabi - Mahatma, Masmuni (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This study aims to explore and analyze the concepts proposed by Al-Farabi regarding the ideal state or virtuous city to enrich our understanding of how Islamic nations can address the challenges of modernity and democracy while maintaining a balanced approach to core Islamic values. This research adopts a literature review methodology, gathering and analyzing various primary and secondary sources related to Al-Farabi's political thoughts on the concept of the ideal state. Al-Farabi's ideas about the ideal state or virtuous city provide essential principles for building a nation that prioritizes the well-being of its society. In the modern context, Al-Farabi's ideas can inspire and guide societies in developing inclusive, just, and sustainable political systems. The holistic concept of political wisdom by Al-Farabi can offer an appropriate framework for inclusive Islamic propagation grounded in various essential principles from Al-Farabi's central city. Applying Al-Farabi's philosophical perspective within the context of propagation enables the Islamic community to navigate the complexities of the modern world while remaining true to their Islamic identity.